Effect of Hydroxyl-Terminated Random Copolyether (PET) and Hydroxyl-Terminated Polybutadiene (HTPB) on Thermal Decomposition Characteristics of Ammonium Perchlorate - Mao, Ke-Zhu; Xia, Min; Luo, Yun-Jun (Journal of Research Updates in Polymer Science, 2015)
The effects of two binders (PET and HTPB) on thermal decomposition characteristics of Ammonium Perchlorate were studied by TG-FTIR, DSC and SEM. When Hydroxyl-terminated polybutadiene (HTPB) mixes with AP, there is no obvious mutual effect in the process of heating, but it happen in the other way when Hydroxyl-terminated random copolyether (PET) mixes with AP. During the heating process of PET-AP mixture, the decomposition of PET occur in advance significantly, so that the porous structure of AP at the low-temperature decomposition stage becomes more significant, the total amount of heat released increases significantly, and the weight-loss ratio of AP about the two stages increases to about 2:1. During the thermal decomposition, the heat release and N2O gas production of PET-AP mixture is milder than the HTPB-AP, which is more conducive to the insensitive properties of propellant.